Replacing what’s lost: a new era of stem cell therapy for Parkinson’s disease - Fan, Yong (Transl Neurodegener, 2020)
BACKGROUND: Stem cells hold tremendous promise for regenerative medicine because they can be expanded infinitely, giving rise to large numbers of differentiated cells required for transplantation. Stem cells can be derived from fetal sources, embryonic origins (embryonic stem cells or ESCs) or reprogrammed from adult cell types (induced pluripotent stem cells or iPSCs). One unique property of stem cells is their ability to be directed towards specific cell types of clinical interest, and can mature into functional cell types in vivo. While transplantations of fetal or ESC-derived tissues are known to illicit a host immunogenic response, autologous transplantations using cell types derived from one’s own iPSCs eliminate risks of tissue rejection and reduce the need for immunosuppressants. However, even with these benefits, cell therapy comes with significant hurdles that researchers are starting to overcome. In this review, we will discuss the various steps to ensure safety, efficacy and clinical practicality of cell replacement therapy in neurodegenerative diseases, in particular, Parkinson’s disease. MAIN BODY: Parkinson’s disease (PD) results from a loss of dopaminergic neurons from the substantia nigra and is an ideal target for cell replacement therapy. Early trials using fetal midbrain material in the late 1980s have resulted in long term benefit for some patients, but there were multiple shortcomings including the non-standardization and quality control of the transplanted fetal material, and graft-induced dyskinesia that some patients experience as a result. On the other hand, pluripotent stem cells such as ESCs and iPSCs serve as an attractive source of cells because they can be indefinitely cultured and is an unlimited source of cells. Stem cell technologies and our understanding of the developmental potential of ESCs and iPSCs have deepened in recent years and a clinical trial for iPSC-derived dopaminergic cells is currently undergoing for PD patients in Japan. In this focused review, we will first provide a historical aspect of cell therapies in PD, and then discuss the various challenges pertaining to the safety and efficacy of stem cell-based cell transplantations, and how these hurdles were eventually overcome. CONCLUSION: With the maturity of the iPSC technology, cell transplantation appears to be a safe and effective therapy. Grafts in non-human primates survive and remain functional for more than 2 years after transplantation, with no signs of tumorigenesis, indicating safety and efficacy of the treatment. However, immunosuppressants are still required because of the lack of “universal stem cells” that would not evoke an immune response. The results of ongoing and upcoming trials by a global consortium known as GForce-PD would be highly anticipated because the success of these trials would open up possibilities for using cell therapy for the treatment of PD and other degenerative diseases.